The Role of Regional Autonomy in Poverty Reducing in Kediri City, East Java - Indonesia - Marwanto, I Gedhe Heru (International Journal of Economics, Business and Management Studies, 2019)
Regional autonomy provides excellent dedication to poverty reducing, especially to realize equity and distribution justice for the poor. As one of the pilot areas, the City of Kediri received much appreciation from the government because of their strategic programs in poverty alleviation. Not without reason, poverty alleviation is an annual agenda of the Indonesian government that continues to experience ups and downs, especially in the face of inflation that is increasingly clear in plain sight. The role of regional autonomy is one of the government's efforts to encourage progress and gain the potential of existing resources, especially productive people and natural resources. The research was conducted based on a literature study to reveal the role of regional autonomy in Kediri City. As an autonomous region that has a variety of potential resources and is able to reduce poverty levels in the region, it will be quite interesting to know the role of local governments in poverty reducing. The results of the study mentioned that the efforts of local governments have a positive role in poverty alleviation through various excellent programs and cooperation of all related parties.